PENGEMBANGAN E-MODUL MENGGUNAKAN CANVA PADA TEMA 4 SEHAT ITU PENTING SUBTEMA 1 PEREDARAN DARAHKU SEHAT - Rany Nuraningsih; Suhendra; Yudhie Suchyadi (STKIP Subang, 2024)
The development of this e-module expects teachers to be more innovative in creating learning, and the development of this e-module is carried out to improve the quality of learning in schools in order to keep up with the increasingly rapid and sophisticated development of educational technology. The method used is the Research and Development (R&D) method. This method uses the ADDIE research model which consists of five steps, namely the analysis stage (analyze), the design stage (design), the development stage (development), the media implementation stage (implementation), and the media evaluation stage (evaluation). In this development research produces e-module teaching material products using Canva on theme 4 healthy is important subtheme 1 healthy blood circulation learning 1 with the content of science and Indonesian lessons. Data from media expert validation results is 100% which means the product is very feasible to implement. The acquisition of linguists is 100% with very feasible interpretation criteria. The material expert obtained a result of 94.5% with very feasible interpretation criteria, and based on the results of distributing student response questionnaires distributed to 35 fifth grade students, the average score data was 90.45% with a score of very feasible to use.